Newborn with Congenital Isolated Radial Nerve Palsy - Lik Han, Ong; Faris Indra Prahasta, Didi Indra; Xi Yuan, Ang (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2022)
Isolated radial nerve palsy in neonate is rare entity due to under-reporting as uniformly it has complete recovery. Theory including radial nerve compression due to isolated compression certain bony prominences intrauterine. Review literature of late only up to 56 cases reported. Despite with conservative management, it shows complete recovery.